2021
DOI: 10.1088/1742-6596/1806/1/012214
|View full text |Cite
|
Sign up to set email alerts
|

Development of STREAM integrated astronomy as an enrichment teaching material for elementary students

Abstract: This study aims to develop STREAM (Science, Technology, Religion, Engineering, Art and Mathematics) integrated thematic learning material with the context of the ring solar eclipse material for elementary students. This type of research is Research and Development (RnD) using ADDIE research design. The experimental subjects used in this study were 40 students at third grade in one of the integrated Islamic elementary schools in Cirebon. Data were collected using interviews, questionnaires, and tests. The instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Harun et al (2020) stated that badminton coaches require high accuracy, consistency, and efficiency in feeding the shuttlecock, thus requiring more training duration than necessary. The badminton coach's ability to feed at a stable and constant speed and angle or direction will be difficult if done for a long period (Kurniawan & Sukardi, 2023). This is normal due to limited conditions or human performance in providing and maintaining concentration and stamina in providing bait or feeding to athletes (Kusnaedi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Harun et al (2020) stated that badminton coaches require high accuracy, consistency, and efficiency in feeding the shuttlecock, thus requiring more training duration than necessary. The badminton coach's ability to feed at a stable and constant speed and angle or direction will be difficult if done for a long period (Kurniawan & Sukardi, 2023). This is normal due to limited conditions or human performance in providing and maintaining concentration and stamina in providing bait or feeding to athletes (Kusnaedi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus supporting a meaningful learning experience and problem solving. Through STREAM, science and technology DOI 10.18502/kss.v7i14.12021 ICESRE 2021 can be interpreted through art and engineering as well as mathematics [35]. STREAM can improve students' critical thinking skills because the collaboration between this model and approach in thematic learning can make students actively participate in learning [36].…”
Section: Discussionmentioning
confidence: 99%
“…So it can be concluded that STREAM is an integrated learning approach that supports students to make broader efforts about the real world situation that is integrated from a religious point of view [14]. STREAM supports meaningful learning experiences and problem solving while still believing that science, technology, engineering, art, religion and mathematics are interconnected.…”
Section: Development Of Stem Steam and Stream Learningmentioning
confidence: 99%